The impact of learning styles in a variety of education and keep the speed performance of Aldharpt in front and transmitter in tennis for students - Hussein, Mohammed (Journal of Physical Education, 2014)
Aims researcher wen wen specialist to arrive at a better extemaRiq methods and models of education to learn skills of sports connect the learner to acqiere arate oryx and mastery and play this is not limited only to learn the skill and mastery but benefit from the model investment of time and effort , the selection of the best model of educational methods to speed up the learning process and increase memory retention skill cognitive performance these methods characterized by learning practical exercies and different images in receiving information and display pictures.